Development of a load monitoring system for residential purposes - Tan, Benny Jian Rong (2016)
As we move towards a sustainable future, efforts are taken upon to improve the overall system efficiency. This is due to the continuous growth unfavourable pattern of loads and consumptions, which led to power utilities operating at low and deteriorating load factor. NALM is the solution for Demand Side Management, which provides the consumer ability to deliberately intervene to their energy usage patterns by making change to their lifestyle. With NALM’s nonintrusive characteristics, it would be widely accepted and applicable to old and existing infrastructure. However, NALM has seen slow adoption rate due to the complexity of the disaggregation techniques. Here, the aim would be to provide a basis by showcasing steady-state disaggregation techniques by having real power as its initial parameter for discerning the active devices. Subsequently, the reactive power parameter is introduce to target overlapping power characteristics. Lastly, practical applications has demonstrated useful to the consumer by developing a graphic user interface which allows interaction by means of setting energy consumption limits and having a feedback system which notifies the user when his pre-set limit is approached or has exceeded. It is evident from the findings that with simple hardware, NALM would be of great convenience to the consumer. It will provide the consumer with vital power usage information and allowing different forms of intervention to his consumption patterns.